Physiotherapy Management of Frozen Shoulder Sinistra Case at Dr. Hardjono Ponorogo Hospital: Case Report - Rahmadhani, Desty Tri; Naufal, Adnan Faris; KIngkinarti, Kingkinarti (FISIO MU: Physiotherapy Evidences, 2023)
Frozen shoulder or adhesive capsulitis is a condition in the form of pain and stiffness that occurs in the shoulder, usually this complaint is caused by a relatively small injury but the causes that often occur are unclear. Physiological problems in frozen shoulder are hypomobility or glenohumeral joint capsular pattern problems. The prevalence of frozen shoulder in Indonesia in the general population is reported to be around 2% with a prevalence of 11% in diabetics. The purpose of this study was to determine the appropriate physiotherapy management in frozen shoulder patients. With the case report research method (case study) conducted on a frozen shoulder patient at Dr. Hardjono Ponorogo which was conducted in January 2023. The results of the study found that physiotherapy interventions in the form of shortwave diathermy (SWD), Myofascial release, and active exercise which were carried out for 3 meetings showed results in the form of reduced pain, increased range of motion of joints, and increased functional ability patient.